Um altar funerário romano em Bustelo: (Penafiel, Porto, Norte de Portugal) - Soeiro, Teresa; Redentor, Armando (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2021)
This paper presents the study of an inscribed Roman funerary altar, found in 2020 in the old monastery of Bustelo (Penafiel). The circumstances of the finding were recorded as well as the possible post-Roman era route of the piece and its reuse. The study of the typological characteristics of the support is carried out and the text is analysed from the epigraphic and historical points of view, seeking to contextualize the monument in the regional epigraphy. Taking into account the current knowledge about Roman sites in the vicinity of the finding place, the potential connexion with contemporary settlements of the altar making and primary use is discussed.